Analisis Customer Relationship Management Terhadap Customer Life-Time Value Dengan Customer Statisfaction Sebagai Variabel Mediasi - Raditya, Dhatu Dara (Green Publisher Indonesia, 2025)
This study analyzes the influence of Customer Relationship Management (CRM) on Customer Lifetime Value (CLV) with Customer Satisfaction (CSF) as a mediating variable. This study was conducted on MVP Coffee Company operating in Mataram City, with the aim of understanding the extent to which the implementation of CRM strategies can increase customer loyalty and long-term economic value generated by customers. The research method used is a quantitative approach with data collection techniques through questionnaires. This study uses a purposive sampling method with a sample of 110 respondents who are customers of MVP Coffee Company who have made more than one visit. The collected data was analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model with SmartPLS software to test the relationship between the study variables. The results of the study show that CRM has a positive and significant influence on CSF and CLV. Furthermore, CSF also acts as a mediating variable that strengthens the relationship between CRM and CLV. In other words, the better the implementation of CRM in the company, the higher the customer satisfaction rate, which ultimately increases CLV. These findings support the relationship-based marketing theory that effective customer relationship management not only improves customer satisfaction but also drives customer loyalty and value in the long run. The implication of this study is the importance of companies in the service industry, especially the café business, to optimize CRM strategies to improve customer experience. Strategies that can be implemented include the use of technology for service personalization, more intensive management of interactions with customers, and the provision of services oriented towards customer satisfaction. In addition, this research provides insights for marketing managers regarding the importance of maintaining long-term relationships with customers as a sustainable business strategy.